Dichotomy of Genetic Abnormalities in PEComas With Therapeutic Implications. (June 2015) - Agaram, Narasimhan P.; Sung, Yun-Shao; Zhang, Lei; Chen, Chun-Liang; Chen, Hsiao-Wei; Singer, Samuel; Dickson, Mark A.; Berger, Michael F.; Antonescu, Cristina R.
<x xml:space="preserve">Abstract</x> Perivascular epithelioid cell neoplasms (PEComa) are a family of rare mesenchymal tumors with hybrid myo-melanocytic differentiation. Although most PEComas harbor loss-of-function TSC1/TSC2 mutations, a small subset were reported to carry TFE3 gene rearrangements. As no comprehensive genomic study has addressed the molecular classification of PEComa, we sought to investigate by multiple methodologies the incidence and spectrum of genetic abnormalities and their potential genotype-phenotype correlations in a large group of 38 PEComas. The tumors were located in soft tissue (11 cases) and visceral sites (27) including uterus, kidney, liver, lung, and urinary bladder. Combined RNA sequencing and fluorescence in situ hybridization analysis identified 9 (23%) TFE3 gene–rearranged tumors, with 3 cases showing an SFPQ/PSF-TFE3 fusion and 1 case showing a novel DVL2-TFE3 gene fusion. The TFE3-positive lesions showed a distinctive nested/alveolar morphology and were equally distributed between soft tissue and visceral sites. In addition, novel RAD51B gene rearrangements were identified in 3 (8%) uterine PEComas, which showed a complex fusion pattern and were fused to RRAGB/OPHN1 genes in 2 cases. Other nonrecurrent gene fusions, HTR4-ST3GAL1 and RASSF1-PDZRN3, were identified in 2 cases. Targeted exome sequencing using the IMPACT assay was used to address whether the presence of gene fusions is mutually exclusive from TSC gene abnormalities. TSC2 mutations were identified in 80% of the TFE3 fusion-negative cases tested. Coexistent TP53 mutations were identified in 63% of the TSC2-mutated PEComas. Our results showed that TFE3-rearranged PEComas lacked coexisting TSC2 mutations, indicating alternative pathways of tumorigenesis. In summary, this comprehensive genetic analysis significantly expands our understanding of molecular alterations in PEComas and brings forth the genetic heterogeneity of these tumors.